(untitled) (Applied Biological Research, 2023)
Silk glands are highly regulated during 5th instar larval development of Bombyx mori. Several genes show up and down regulation in silk glands during 5th instar stage. Nuclear matrix tethers chromatin and marks them into active and inactive domains, thereby playing an important role in gene regulation. The association of differentially regulated genes of silk glands to nuclear matrix has not been studied earlier. The present study explored the binding of genes to nuclear matrix and their differential expression. The association to nuclear matrix of the selected genes was studied using in-silico methods. The MAR Finder analysis showed high MAR binding potential for all the genes selected. The number of MAR binding sites varied from day 1 to day 7. Differences were observed in MAR sites during development often coincided with differential expression of genes. This study gives a new perspective in the understanding of differential gene regulation in silk gland development.